2016
DOI: 10.1039/c6tb01362g
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical fabrication of calcium phosphate-based thin layers and nanospheres using laser processing in solutions

Abstract: We achieved simple and rapid fabrication of calcium phosphate (CaP)-based thin layers and nanospheres by laser processing in supersaturated solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 97 publications
(173 reference statements)
0
17
0
Order By: Relevance
“…Conventional biomimetic processes are weak in productivity, which require a fairly long processing period (more than a day) because of multi-step procedures and slow CaP growth rate in the immersion step. Recently, we combined a laser process with a biomimetic process to achieve facile single-step CaP coatings on several artificial materials [ 24 28 ] by refining earlier techniques proposed by Pecheva et al . [ 29 ] and Lee et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional biomimetic processes are weak in productivity, which require a fairly long processing period (more than a day) because of multi-step procedures and slow CaP growth rate in the immersion step. Recently, we combined a laser process with a biomimetic process to achieve facile single-step CaP coatings on several artificial materials [ 24 28 ] by refining earlier techniques proposed by Pecheva et al . [ 29 ] and Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to apply the LAB process for CaP coating to PEEK substrates and to demonstrate the improved biological properties of the resulting material. The LAB process has been applied to several artificial materials with laser absorption [ 24 28 ]. However, its applicability to chemically unreactive PEEK remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Ansar et al reported one-pot fabrication of IO-loaded CaP particles, however, their processing time was as long as a day [17]. We recently developed a facile one-pot fabrication process of CaP-based submicrospheres containing IO nanoparticles (denoted by IO-CaP submicrospheres) using a laser-assisted precipitation process (Figure 1a) [18,19]. In this process, weak pulsed laser irradiation was applied to a pH-controlled labile CaP reaction mixture (a mixture of calcium and phosphate ion solutions) supplemented with ferrous ions (Fe 2+ ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the coating medium should contain no harmful components and must be intraorally administrable. Recently, the authors developed a CaP coating technique using a laser-assisted biomimetic (LAB) process that satisfies these requirements [ 11 , 12 , 13 , 14 , 15 , 16 ]. In the LAB process, a weak pulsed Nd:YAG laser is used to irradiate the target region of an artificial material immersed in a supersaturated CaP solution.…”
Section: Introductionmentioning
confidence: 99%